Trade liberalization, price transmission and household welfare: evidence from China - Zhang, Teng; Zhou, Dai; Xu, Shu; Xu, Zhiwei (Technological and Economic Development of Economy, 2025)
This paper estimates the welfare effect of trade through the price channel by jointly considering the consumption and income effect. The consumer price data and household survey data of China are used to conduct the empirical analysis. For assessing the consumption effect, the quadratic almost ideal demand system (QUAIDS) model is used to capture the substitution effect of price changes. We find that every household of China is better off due to the reduction of import tariffs, but there is a strongly pro-poor bias. More importantly, ignoring the substitution effect on the consumption side not only underestimates the absolute value of welfare changes but also distorts the distribution of welfare changes. Our results imply the importance of the consumption effect in estimating the welfare gain of households from trade liberalization. Our framework can also be extended to assess consequences of the opening policies of other economies. First published online 05 June 2025